О гарпактикоидах (Crustacea, Награсticoidea) советского участка низовьев Дуная и его дельты - Монченко, В.И.; Полищук, В.В. (Вестник зоологии, 1969)
The authors found 35 harpacticoid copepod species in the investigated region. The males of Schizopera borutzkyi Mo n t s c h e n к o, 1967, that were unknown earlier, are found for the 4irst time. The morphological peculiarities of those males and the details ol the external structure of Nannopus palustris (Brady. 1880) females are described. Altogether 40 harpacticoid species are now known in the above-mentioned region.